Influence of diabetes on autonomic function in children: Analysis through the geometric indices - Giacon, Thais Roque [UNESP]; Vanderlei, Franciele Marques [UNESP]; Da Silva, Anne Kastelianne França [UNESP]; Da Silva, Natália Turri [UNESP]; Valenti, Vitor Engrácia [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Faculdade de Filosofia e Ciências, 2016)
Introduction: Diabetes mellitus type 1 has been established as one of the most common noncommunicable diseases among children, diabetic autonomic dysfunction presenting as one of its most frequent complications, however, few studies have evaluated autonomic modulation through heart rate variability in diabetic children. Objective: To analyze the autonomic modulation in children with diabetes mellitus type 1. Methods: Data from 36 children of both sexes were analyzed, who were divided into two groups: Diabetes mellitus type 1, n = 13 (11.62 ± 2.18) with a diagnosis of Diabetes mellitus type 1 and control, n = 23 (11.04 ± 1.02) without the disease. Initially personal data, weight, height, heart rate and blood pressure were collected. Subsequently, for the analysis of autonomic modulation, the heart rate beatto- beat was captured using a heart rate monitor in the supine position for 30 minutes. The geometric indices (RRtri, TINN, Poincaré plot) were calculated to analyze autonomic modulation. The Student t test for parametric data or the Mann-Whitney test for nonparametric data, with a 5% signifi cance level, were used for comparison between groups. Results: The results demonstrated a reduction in RRtri, TINN, SD1 and SD2 in diabetic children. The SD1/SD2 ratio was similar between groups. In the qualitative analysis of the Poincaré plot, the children with Diabetes mellitus type 1 presented a fi gure with less dispersion of the points when compared to the control children. Conclusion: Children with diabetes mellitus type 1 have reduced overall variability and parasympathetic modulation.
Keywords: Autonomic nervous system; Child; Diabetes mellitus type 1